Fingolimod for multiple sclerosis and emerging indications: appropriate patient selection, safety precautions, and special considerations - Ayzenberg I; Hoepner R; Kleiter I (Dove Medical Press, 2016)
Ilya Ayzenberg, Robert Hoepner, Ingo Kleiter Department of Neurology, St Josef Hospital, Ruhr University Bochum, Bochum, Germany Abstract: Fingolimod (FTY720), an immunotherapeutic drug targeting the sphingosine-1-phosphate receptor, is a widely used medication for relapsing-remitting multiple sclerosis (MS). Apart from the pivotal Phase III trials demonstrating efficacy against placebo and interferon-β-1a once weekly, sufficient clinical data are now available to assess its real-world efficacy and safety profile. Approved indications of fingolimod differ between countries. This discrepancy, to some extent, reflects the intermediate position of fingolimod in the expanding lineup of MS medications. With individualization of therapy, appropriate patient selection gets more important. We discuss various scenarios for fingolimod use in relapsing-remitting MS and their pitfalls: as first-line therapy, as escalation therapy after failure of previous immunotherapies, and as de-escalation therapy following highly potent immunotherapies. Potential side effects such as bradycardia, infections, macular edema, teratogenicity, and progressive multifocal leukoencephalopathy as well as appropriate safety precautions are outlined. Disease reactivation has been described upon fingolimod cessation; therefore, patients should be closely monitored for MS activity for several months after stopping fingolimod. Finally, we discuss preclinical and clinical data indicating neuroprotective effects of fingolimod, which might open the way to future indications such as stroke, Alzheimer’s disease, and other neurodegenerative disorders. Keywords: immunotherapy, bradycardia, progressive multifocal leukoencephalopathy, neuroprotection, stroke, Alzheimer’s disease